2012
DOI: 10.1049/mnl.2012.0590
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation and comparison with experimental characterisation of side gate p-type junctionless silicon transistor in pinch-off state

Abstract: A side gate p-type junctionless silicon transistor is fabricated by atomic force microscopy nanolithography using a anisotropic potassium hydroxide wet etching process on low doped (10 5 cm 23 ) silicon-on-insulator wafer. The structure is a gated resistor and turns off based on a pinch-off effect principle, when essential positive gate voltage is applied and made a sufficiently large barrier in the gating region. Negative gate voltage is unable to make a significant impact on drain current to drive the device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The coating layer also enhances the laser reflectivity of the cantilever. In fact, Cr/Pt and Au coated probe showed the acceptable result [33][34], but the Al reflex coating did not provide any acceptable results. Another issue is the order of oxidation.…”
Section: Methodsmentioning
confidence: 90%
“…The coating layer also enhances the laser reflectivity of the cantilever. In fact, Cr/Pt and Au coated probe showed the acceptable result [33][34], but the Al reflex coating did not provide any acceptable results. Another issue is the order of oxidation.…”
Section: Methodsmentioning
confidence: 90%
“…Low doping concentration is implemented in this work to control the scattering effect in the channel and avoid using high-cost material which usually is associated with the high-doped silicon technology. The operation of the device towards pinch off (Sorée et al , 2010) was previously investigated in the study by Dehzangi et al (2012). In this paper, we investigate the performance of SGJLT in the accumulation region.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the researchers of the present study have reported the fabrication and experimental characterization of low doped p-type junctionless transistors with single and double lateral gate(s) through the unconventional method of atomic force microscopy (AFM) nanolithography [15] , [16] , [17] . Simulations of carrier's transport and pinch off mechanism of the device have been presented in Refs.…”
Section: Introductionmentioning
confidence: 99%